The broken bow [large type] - Sweazy, Larry D. (A Trusty Dawson, U.S. Deputy Marshal western, 2022)
"U.S. Marshal Sam Trusty Dawson finds himself targeted for vengeance with his face on a wanted poster. Now he's up against every cutthroat gunslinger willing to put a bullet through his badge for the bounty . . . Theodore Marberry is a grieving father. He groomed his daughter Jessica to take her rightful place among the wealthy families of St. Louis high society. Instead she fell in love with a common lawman. She lost her life bringing his child into the world. Although bestowed with a beautiful granddaughter, Marberry is consumed with hate towards the baby's father. Deputy U.S. Marshal Sam "Trusty" Dawson lives under a death sentence. His only crime was falling in love with a woman who saw more worth in his character than in his bank account. Now, every deadly manhunter, desperate bushwacker, and vicious outlaw throughout the Dakota Territory is looking to put the lawman six feet under to collect "--